2015
DOI: 10.1111/are.12894
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial communities in intensive GIFT tilapia (Oreochromis niloticus) pond systems during the peak period of breeding

Abstract: Aquaculture pond is a complex ecosystem where the microorganisms in the sediments, in the animal intestinal tract and in water interact with each other to influence the water quality and health of aquatic animals. In order to understand the spatial distribution and relationship of microbial communities in intensively farmed genetically improved farmed tilapia (GIFT, Oreochromis niloticus), 454 high-throughput pyrosequencing was applied to analyse the 16S rRNA gene of bacteria in intensive GIFT ponds in Wuxi Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 41 publications
6
32
2
2
Order By: Relevance
“…In this study, Fusobacteria represented 36%, while other authors such as Fan et al () reported 26%, Zhai et al () 56%, Gaikwad, Shouche, and Gade () 45% or Ran et al () 34%. Although not all samples of the present study responded to this pattern, high values of Fusobacteria seem characteristic of Oreochromis sp., especially compared to other species like H. molitrix <12% (Ye, Amberg, Chapman, Gaikowski, & Liu, ), S. salar <7% (Dehler, Secombes, & Martin, ; Gajardo et al, ) or O. mykiss <1% (Huyben et al, ).…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…In this study, Fusobacteria represented 36%, while other authors such as Fan et al () reported 26%, Zhai et al () 56%, Gaikwad, Shouche, and Gade () 45% or Ran et al () 34%. Although not all samples of the present study responded to this pattern, high values of Fusobacteria seem characteristic of Oreochromis sp., especially compared to other species like H. molitrix <12% (Ye, Amberg, Chapman, Gaikowski, & Liu, ), S. salar <7% (Dehler, Secombes, & Martin, ; Gajardo et al, ) or O. mykiss <1% (Huyben et al, ).…”
Section: Discussioncontrasting
confidence: 44%
“…In this study, Fusobacteria represented 36%, while other authors such as Fan et al (2015) (Dehler, Secombes, & Martin, 2017;Gajardo et al, 2016) or O. mykiss <1% (Huyben et al, 2017). Merrifield and Ringo (2014) argue that the average content of Fusobacteria in common commercial fish is below 7%.…”
Section: Supplementation With a Platensis Improved Growth Rates Andcontrasting
confidence: 53%
See 1 more Smart Citation
“…Qin et al () reported that the abundance of bacterial 16S rRNA genes in ponds with grass carp ( Ctenopharyngodon idellus ) fed Sudan grass was significantly lower than that in ponds with grass carp fed commercial feed. In previous studies, significant changes were observed in the microbial community under different stocking densities in tilapia fishponds (Fan, Barry, et al, ; Fan, Chen, et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…Microbes play a vital role in the conversion and metabolism of organic matter in aquaculture environments and are considered to be sensitively influenced by changes in aquaculture activities (Lücker et al, ; Pantoja, Sepúlveda, & González, ; Rodriguez‐Brito et al, ; Stephens et al, ; Xia et al, ). For example, the design of rearing systems, the supplementation of formulated feed, and different stocking densities can alter microbial community assemblies in fishponds (Fan, Chen, et al, ; Giatsis et al, ; Qin et al, ). Giatsis et al () reported that the steering of the microbial community in the gut of Nile tilapia ( Oreochromis niloticus ) could be possible through water microbial management derived by the rearing environment.…”
Section: Introductionmentioning
confidence: 99%